2011
DOI: 10.1002/adma.201102619
|View full text |Cite
|
Sign up to set email alerts
|

Indigo ‐ A Natural Pigment for High Performance Ambipolar Organic Field Effect Transistors and Circuits

Abstract: Millenniums-old natural dye indigo--a "new" ambipolar organic semiconductor. Indigo shows balanced electron and hole mobilities of 1 × 10(-2) cm(2) V(-1) s(-1) and good stability against degradation in air. Inverters with gains of 105 in the first and 110 in the third quadrant are demonstrated. Fabricated entirely from natural and biodegradable compounds, these devices show the large potential of such materials for green organic electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
339
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(348 citation statements)
references
References 32 publications
5
339
0
4
Order By: Relevance
“…Chemical investigation and archaeological evidence have shown that purple was widely spread after the deposition of the body for burial. These results are the earliest chemical evidence of purple colorant used during funeral rituals (not as textile dye) and enabled us to highlight new aspects of funeral practices in Roman times [30] .…”
Section: Tyrian Purplementioning
confidence: 74%
See 1 more Smart Citation
“…Chemical investigation and archaeological evidence have shown that purple was widely spread after the deposition of the body for burial. These results are the earliest chemical evidence of purple colorant used during funeral rituals (not as textile dye) and enabled us to highlight new aspects of funeral practices in Roman times [30] .…”
Section: Tyrian Purplementioning
confidence: 74%
“…During the past 30 years, a core group of marine natural products (MNPs) chemists from several countries, in collaboration with both academic pharmacologists and the pharmaceutical industry, have reported a very large number of novel metabolites with useful and sometimes sensational pharmacological properties. However, MNPs are exhibiting high antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%
“…Indigo is a well-known natural dye used in blue jeans, and even this molecule itself shows ambipolar transport. 4 Isoindigo is an isomer with the same molecular formula, and copolymers with fluorene or benzothiadiazole show ambipolar characteristics with the mobilities exceeding 0.1 cm 2 V ¹1 s …”
mentioning
confidence: 99%
“…Hole and electron mobility of 0.01 cm 2 V ¹1 s ¹1 has been observed in indigo, 103 which is a dye used in blue jeans, and the characteristic deep blue color comes from the small HOMO LUMO gap of 1.7 eV. We have improved the ambipolar operation to 0.56/0.95 cm 2 V ¹1 s ¹1 and 0.42/0.85 cm 2 V ¹1 s ¹1 , respectively in diphenyl and diiodo-indigo.…”
mentioning
confidence: 99%
“…101 Recently, high-performance ambipolar transistors have been realized using donor-acceptor polymers. 102 Among small molecules, stable ambipolar transistors have been achieved using a passivation layer of tetratetracontane (TTC, C 44 H 90 ), 103,104 where even pentacene shows ambipolar characteristics. 105 The operation regions of an ambipolar transistor are divided as shown in Figure 16 depending on the polarity of the gate voltage V G and the drain voltage V D , 106 where it is important to consider nonzero electron and hole threshold voltages, V T and V T ¤.…”
mentioning
confidence: 99%